Media Freedom is the Primary Culprit for Depressive Disorders: A Cross-National Analysis. (13th November 2019) - Lin, Y C; Yan, H T
Abstract: Background: There has been much speculation about social environments causing an epidemic of depression. The objectives of this study are to examine how media freedom influences prevalence of depressive disorders. A direct effect of free media is great levels of information complexity causing poor mental health. Two indirect effects are that media freedom facilitates modernization, which is associated with competition-related stress, and government investment in social protection, which impedes the person's ability to manage stress. Methods: The study used a cross-sectional analysis on determinants of prevalence of depressive disorders in 2015 covering 98 democratic countries. Media freedom was measured as the degree to which a country allows the freedom of news and information of print media, television, and radio broadcasting (0-100: least to most free). Control variables were then added, including GDP per capita growth, population density, country latitude, and religious affiliations. Further, a mediation analysis was applied to test if there is a causal pathway that links the degrees of media freedom and the levels of economic development or/and social protection to prevalence of depression. Results: We found that an increase in the score of media freedom by 10 resulted in a 0.20 percentage point increase in prevalence of depressive disorders (%) (0.20, CI = 0.10-0.30). Our theoretical expectations were still confirmed when this study examined the relationship for each year between 2011 and 2014 (e.g. in 2014, 0.19, CI = 0.09-0.29), used an alternative index of media freedom from a practitioners' view (0.17, CI = 0.02-0.32), or measured each country's level of internet and digital media freedom (0.30, CI = 0.10-0.49). Further, a mediation test showed that 39.88% and 21.38% of the total effect was mediated through the economic and social pathway respectively. Conclusions: The findings suggest that great levels of media freedom matter in increasing prevalence of depression. Key messages: Great levels of media freedom matter in increasing prevalence of depression. There are direct and two indirect effects of media freedom on prevalence of depression.